Study on optimization and mechanism of CO2 injection to enhance oil recovery in mid-deep heavy oil reservoirs - Zhang, Xiaokun; Qi, Zongyao; Wang, Bojun; Zhou, You; Wang, Chao; Xi, Changfeng; Liu, Pengcheng (Frontiers in Energy Research, 2024)
Abstract：In order to improve the oil recovery of mid-deep heavy oil reservoirs, this study investigates the efficiency of enhanced oil recovery and the mechanisms of oil displacement in middeep heavy oil reservoirs using different injected gases (N2, CH4, CO2) and development approaches (gas flooding and gas huff-n-puff) through a series of experiments. These experiments include highpressure physical properties tests of crude oil after gas injection, displacement efficiency tests of gas injection, and displacement efficiency tests of gas huff-n-puff. The results indicate that for middeep heavy oil reservoirs, the preferred optimal injection gas is CO2, with gas huff-n-puff being the most effective development method. Furthermore, a numerical simulation study was conducted to explore the adaptability parameters of CO2 huff-n-puff development in different well patterns, encompassing variables such as the amount of gas injected per cycle, crude oil viscosity, reservoir permeability, and oil layer thickness.